Optoelectronic resonant tunneling diodes for high purity oscillations and excitable pulse generation - Romeira, B.; Figueiredo, J.; Javaloyes, J.; Balle, S.; Piro, O.; Ironside, Charlie (2013)
We investigate the dynamics of optoelectronic oscillators (OEOs) employing high-speed resonant tunneling diodes (RTDs) integrated with a laser diode. This RTD-OEO excitable system is analyzed in the context of two applications: ultra high spectral purity microwave generation for sensing and telecommunication networks and high-speed excitable pulse generation for biologically inspired information processing.